Evaluation of client progress in music therapy: an illustration of an N-of-1 design in individual short-term improvisational music therapy with clients with depression. Issue 3 (27th May 2017) - Aalbers, Sonja; Spreen, Marinus; Bosveld-van Haandel, Linda; Bogaerts, Stefan
ABSTRACT: This article introduces music therapy clinicians to a research design that can be easily implemented in clinical practice to evaluate and monitor the impact of interventions on individual clients: the systemic N-of-1 design. In this single-case design, the client's network, consisting of professional and non-professional network members, assumes the role of evaluators of the given treatments. The systemic N-of-1 design is illustrated with a small empirical study with nine clients with symptoms of depression within a single private practice. The study participants received individual short-term improvisational music therapy (ISIMT) consisting of seven weekly sessions. One week before the first session and one week after the last session, the Inventory of Depressive Symptomatology (IDS) was completed by the clients, their professionals and network members. Applying the systemic N-of-1 design produced valuable individualised and group information about the effects of ISIMT on depressive symptoms. The systemic N-of-1 design can be used in clinical practice by music therapists to systematically monitor the outcome of their therapies. Pooling systemic N-of-1 designs by collaborating music therapists may provide valuable information about the efficacy of music therapy.